Assistive technology as an accommodation on accountability assessments: an analysis of attitudes and knowledge of special education professionals - Atchison, Bradley Tilman (Kansas State University, 2008)
No Child Left Behind legislation has required public schools to increase efforts to measure and track student performance through school, district, state and nation-wide assessments. Researchers argue that it is essential for all students, including special education students, to be included in accountability assessments in order to help measure and track educational progress and compare the performance of schools, districts and states in terms of achieving educational goals. One method for including more special needs students in accountability assessments is to use accommodations during testing. Assistive technology is an accommodation that is approved for use on accountability assessments in many states and has the potential to significantly impact the performance of special education students. The primary purpose of this research was to gather and analyze data from special service providers (staff of a special education cooperative) and educators and administrators (employees of the school districts the cooperative serves) on the subject of using assistive technology as an accommodation on Colorado State Assessment Project (CSAP) testing. The researcher conducted a survey to measure the attitudes and knowledge of educators and special service providers on this subject. The survey was a five point Likert scale comprised of ten items designed to measure "attitudes" and ten items designed to measure "knowledge". Data was analyzed using backward regression analysis to compare scores between groups and consider the impact that years of work experience had on survey scores. The researcher used responses from survey data to select ten survey respondents to participate in in-depth interviews. Interview data was analyzed using pentadic analysis, a method of rhetorical analysis designed by Kenneth Burke (1945). Survey results indicated that the knowledge and attitudes scores between the two groups were similar, however regression analysis identified a significant increase the attitude scores of employees of the special education cooperative as they gained work experience. Scores of district employees did not increase on either scale as participants gained work experience. Analysis of interview data provided rich description of participants’ knowledge and attitudes concerning the use of assistive technology as an accommodation and enabled the researcher to identify significant similarities and differences between groups of employees and the state standards intended to guide their decision making on this subject. Results of this research suggest a need for improving education on the subject of assistive technology, related state regulations and improving resources to foster the use of assistive technology as an accommodation on accountability assessments.
Keywords: assistive technology; accountability assessments; attitudes; knowledge; Kenneth Burke; special education; Education, Special (0529); Education, Technology (0710)